Inhibin B as a Marker of Sertoli Cell Damage and Spermatogenic Disturbance in the Rat. (24th January 2013) - Pfaff, Tamara; Rhodes, Jon; Bergmann, Martin; Weinbauer, Gerhard F.
<x xml:space="preserve">Abstract</x> This study was designed to determine the effects of Compound A on spermatogenesis including assessment of inhibin B levels and on fertility in the male rat over a 15 to 19 weeks treatment and a 19 weeks treatment‐free period in control and 30, 60, and 180 mg/kg dose groups (n = 22/group). Compound A in a dose‐dependent manner induced various degrees of spermatogenic alterations compatible with Sertoli cells being the primary target, for example, inter‐ and intracellular Sertoli cell vacuolization and altered cellular morphology followed by germ cell degeneration and marked reduction of epididymidal sperm numbers. Blood–testis barrier remained intact (electron microscopy and hyperosmotic fixation test) until germ cells disappeared. Mating behavior and weights of androgen‐dependent prostate and seminal vesicles remained unaffected. Inhibin B levels correlated only with moderate to severe spermatogenic alterations. Ten animals with inhibin B levels below detection limit were encountered and five of these animals were fertile in week 19 but following 19 weeks without treatment, another five animals were rendered infertile and inhibin B levels remained undetectable. In the rat, inhibin B only reflects major spermatogenic alterations and markedly reduced inhibin B levels might indicate irreversibility of these alterations and even infertility.